KATEGORISASI FILM BERDASARKAN DIALOG DALAM CERITA FIKSI NARASI - Sigit Kusumanugraha (CALACCITRA: JURNAL FILM DAN TELEVISI, 2023)
Categorization for films are generally dividing the genres into two categories, silent film and film with dialogues. However, due to recent development, there are many variations of how a story was told, either it’s a silent film or using sounds. In this journal, the writer will classify more detailed other ways to present dialogues inside a story of a film based on sound, language, and the content which are to be conveyed to the audience. The source validation are from the movies which has already shown in the theatre, or streaming. With this classification, both the filmmaker and audience’s knowledge can be broaden, and also more creative to create films which is aware of the elements inside.